Upper respiratory tract infections in sport and the immune system response. A review - Cicchella, A.; Stefanelli, C.; Massaro, M. (Biology, 2021)
Immunity is the consequence of a complex interaction between organs and the environment. It is mediated the interaction of several genes, receptors, molecules, hormones, cytokines, antibodies, antigens, and inflammatory mediators which in turn relate and influence the psychological health. The immune system response of heavily trained athletes resembles an even more complex conditions being theorized to follow a J or S shape dynamics at times. High training loads modify the immune response elevating the biological markers of immunity and the body susceptibility to infections. Heavy training and/or training in a cold environment increase the athletes` risk to develop Upper Respiratory Tract Infections (URTIs). Therefore, athletes, who are considered healthier than the normal population, are in fact more prone to infections of the respiratory tract, due to lowering of the immune system in the time frames subsequent heavy training sessions. In this revision we will review the behavioral intervention, including nutritional approaches, useful to minimize the "open window" effect on infection and how to cope with stressors and boost the immune system in athletes.